2022
DOI: 10.1039/d1ta09645a
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring atomically dispersed cobalt–nitrogen active sites in wrinkled carbon nanosheets via “fence” isolation for highly sensitive detection of hydrogen peroxide

Abstract: Stable and highly sensitive determination of hydrogen peroxide (H2O2) is needed in various fields ranging from disease prevention to environmental protection. The construction of inexpensive and highly active transition-metal-based nitrogen-doped...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 48 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…Then, the strong interaction between N and NPs can also improve the stability of supported NPs. In published works, it was confirmed that N-doped carbon materials were an excellent support for the dispersion of Pt, Pd, Ru, Cu, , ZnO, and so forth. These hybrids exhibited prominent performance in heterogeneous catalysis, energy storage, sensors, and drug-delivery platforms. …”
Section: Introductionmentioning
confidence: 99%
“…Then, the strong interaction between N and NPs can also improve the stability of supported NPs. In published works, it was confirmed that N-doped carbon materials were an excellent support for the dispersion of Pt, Pd, Ru, Cu, , ZnO, and so forth. These hybrids exhibited prominent performance in heterogeneous catalysis, energy storage, sensors, and drug-delivery platforms. …”
Section: Introductionmentioning
confidence: 99%
“…Such behavior may be related to the formation of CoN sites This journal is © The Royal Society of Chemistry 2023 during pyrolysis, which have been shown to electrochemically catalyze H 2 O 2 oxidation. [100][101][102] In this regard, the formation of CoN during pyrolysis was demonstrated by spectroscopic data (Fig. 4).…”
mentioning
confidence: 85%
“…Hu et al also explored controllably dispersed atomic Co-N sites on nitrogen-doped carbon nanosheets by a dual-template (ZIF and g-C 3 N 4 ) method. 171 The catalyst with 4% Co (44% Co would aggregate into NPs) achieved a high sensitivity of 605.50 mA mM À1 cm À2 for 0.5 Â 10 À3 -1 Â 10 À1 M H 2 O 2 and a low LOD of 6.18 Â 10 À9 M.…”
Section: Sac-based Liquid Sensingmentioning
confidence: 99%
“…Cobalt is highly selective for two-electron transfer, which can provide adequate sites for H 2 O 2 sensing. [168][169][170][171] Our group developed an atomic Co-N x -C site anchored neuronal-like carbon-modified amperometric sensor (Fig. 16c), which exhibited a broad detection range (250 nM-50 mM), high sensitivity (743.3 mA mM À1 cm À2 ), strong selectivity, robust reliability (2.86% decay for one week) and fast response (5 s) for residual H 2 O 2 detection.…”
Section: Sac-based Liquid Sensingmentioning
confidence: 99%